Adaptations of multinational subsidiaries for surviving host country crises: a case study of Venezuela. (4th October 2022) - Garcia, Fernando; Hammontree, Maria Carolina Duarte; Duarte, Pedro; Helms, Marilyn M.
This study examines Venezuelan subsidiaries of multinational enterprises, analysing how companies adapt and survive in adverse business environments. Despite the prolonged, persistent Venezuelan crisis, there are multinationals that remain operational while facing government intervention threats, rampant inflation, currency shortages, and unfavourable labour laws. Using a case study approach, four subsidiaries are explored through face-to-face and telephone interviews with company managers, each representing distinct economic activities and business sectors. We found companies surviving the Venezuelan crisis developed new adaptation capabilities, including the ability to shorten the existing power distance, substitute limited resources, retain key talent, and obtain alternate funding sources. Understanding how these adaptation capabilities allow firms to operate in crisis provides valuable insights for managers and academicians and advances crisis management literature. Practical implications and areas for future research are discussed.